Nonlinear integral equations and its relations with differential equations - Eshkuvatov, Zainidin K. (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2010)
In this paper the brief historical introduction of linear and nonlinear integral equations and its close relations with ordinary or partial differential equations with some examples are described in Section I. Moreover Newton-Kantorovich method and fixed point method are discussed in detail in Section II. Resent development method and its applications for solving Nonlinear integral equation are discussed in Section III. Finally some problems in nonlinear integral equations are given in Section IV followed by conclusion.